Rhetorical Education from Greece to Rome: the Case of Cicero’s "De inventione" - Raschieri, Amedeo (Ciceroniana On Line, 2017)
The case of Cicero’s De inventione is interesting for many reasons. First, the work is an early example of the construction of cultural memory in the field of Roman rhetoric. Second, this work shows a strong connection between rhetorical theory, the Ciceronian interest in other disciplines (especially philosophy) and the oratorical formation of a young Roman in the person of its author. Third, in the De inventione , through the organisation of rhetoric, Cicero collects a significant amount of information about history, literature and law, and, in this way, he preserves these notions for the following decades. Finally, although Cicero rejected the work later in his life, the De inventione was an important moment for the dissemination of rhetoric in Rome and has been remembered as a fundamental work for the study of this discipline in Latin. In order to develop these topics, the paper intends to investigate how Cicero uses the examples derived from myth, history and legal practice, and how philosophy fits for his explanation of rhetoric.